Salt-driven, thin-skinned tectonics and inherited deep seated fault-driven thick tectonics in the Dezful Embayment (Zagros, Iran), illustrated by regional 2D geomechanical restoration - Legrand, X. (TRABAJOS DE GEOLOGÍA, 2009)
Two-dimensional geomechanical reconstructions across the Front Flexure of the Zagros Mountains (Iran), based on 2D regional seismic interpretation, were carried out to investigate the salt kinematics and the influence of inherited structures at depth in the Dezful Embayment. This study identified a positive structural inversion related to detachment within the evaporites of the Miocene Gachsaran formation and diachronism in the deformation from NE to SW. Disharmonic tectonism was also observed, leading to a singular vertical succession with anticlines in deeper limestones (reservoirs) underneath shallow synclines. Finally, an earlier deformation controlled by previous deep-seated faults was proposed to explain the oil traps.